The Influence of Store Atmospheric Factors toward Customer Purchase Intention on Minimarket Industry in Bandung, Indonesia (Alfamart and Circle K Comparison) - Muhammad Iftizal Ghifari; Deddy Saefulloh (Politeknik Negeri Bandung, 2018)
Minimarket industry in Indonesia is hardly a friendly environment for international brand. Not so long ago, one of the well-known global minimarket brand has declared bankruptcy, confirmed that the international brands often find it difficult to maintain and expand the market in overseas. Thus, a new method and strategy have to be done, in order to survive in the industry. One of the main trait for retail industry is the store atmosphere. The surroundings could be explored to influence and attract customer into buying the products. Thus, this study aims to examine store atmosphere’ influence towards customer purchase intention. The objectives of this study are to assess and measure the factors of store atmosphere and how their influence toward customer purchase intention on Alfamart and Circle K outlets. Using multiple linear regression analysis on SPSS to 314 questionnaire data that collected in Bandung, Indonesia, the result of this study is that in-store, ambient cue, and out-store factor has a significant impact toward customer purchase. These findings offers empirical evidence for both academical and business practice regarding the store atmosphere and its influence towards customer purchase intention.